1990
DOI: 10.3109/00498259009046839
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies scaling and comparisons in drug development and toxicokinetics

Abstract: 1. Methods of interspecies extrapolation using physiological models and allometric scaling have been reviewed with their possible application to drug development, both for candidate drug selection and the interpretation of toxicokinetic data. 2. Physiological models offer a mechanistic approach to extrapolation from one species to another, examining individual components which interrelate to produce the characteristics of the whole system. Tissues of interest are arranged in anatomical order based on blood cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 35 publications
1
80
0
1
Order By: Relevance
“…Treatment of the animals was in accordance with regulations outlined in the USDA Animal Welfare act and the conditions specified in The Guide for Care and Use of Laboratory Animals (Institute of Laboratory Animal Research, 1996).…”
Section: Pharmacokinetics/pharmacodynamics In the Cynomolgus Monkeymentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of the animals was in accordance with regulations outlined in the USDA Animal Welfare act and the conditions specified in The Guide for Care and Use of Laboratory Animals (Institute of Laboratory Animal Research, 1996).…”
Section: Pharmacokinetics/pharmacodynamics In the Cynomolgus Monkeymentioning
confidence: 99%
“…In this equation, A is the coefficient (y-axis intercept), B is body weight, and a is the power function (slope) (Ings, 1990). Regression analysis showed that clearance is strongly correlated with body weight across species.…”
Section: Dosing Strategy For Phase I Interspecies Scalingmentioning
confidence: 99%
“…For this experiment, four squirrel monkeys were used. Three of the four animals had participated in prior substituted amphetamine toxicity studies (Table 1); all other experiments reported in this Mordenti and Chappell, 1989;Ings, 1990;Boxenbaum and DiLea, 1995;Mahmood, 1999Mahmood, , 2002Mahmood et al, 2003). Each monkey was administered a dose calculated using their individual weight at the time of administration.…”
Section: Single Dose/route Of Administration Studymentioning
confidence: 99%
“…One difference appears to be that 'equivalent' single doses produce higher plasma concentrations of MDMA in the squirrel monkey than in the human. For example, the 7.4 mg/kg dose in the monkey, estimated to be comparable to a 2 mg/kg dose in a human by the allometric method (for discussion of the method, including its limitations, see Mordenti and Chappell, 1989;Ings, 1990;Boxenbaum and DiLea, 1995;Mahmood, 2002;Mahmood et al, 2003) produced a C max of 773 ng/ml (Figure 1), whereas the 'equivalent' dose in humans (150 mg given to two subjects weighing approximately 75 kg) produced a C max ranging from 442 to 487 ng/ml (de la Torre et al, 2000). The higher plasma MDMA concentration in squirrel monkeys than humans could reflect limits of sample size, limitations of interspecies dose scaling methods using an allometric equation, or effects of stress of our experimental procedures (Johnson et al, 2004).…”
Section: Comparison To Laboratory Human Studiesmentioning
confidence: 99%
“…Allometric interspecies scaling is based on the fact that the regression of the logarithm of a pharmacokinetic parameter and the logarithm of species weight is generally linear. As a result, pharmacokinetic (and therefore pharmacodynamic, including toxicity) parameters for a given drug can be estimated in any species if this linear relationship is determined (Ings 1990). Yates and Kugler (1986) and others have criticized the potential inaccuracy of interspecies scaling, noting the 10-fold range of estimates that may be derived depending on which pharmacokinetic and corrective factors are thought relevant.…”
Section: Responsementioning
confidence: 99%